2014
DOI: 10.3390/metabo4020465
|View full text |Cite
|
Sign up to set email alerts
|

Breath Analysis in Disease Diagnosis: Methodological Considerations and Applications

Abstract: Breath analysis is a promising field with great potential for non-invasive diagnosis of a number of disease states. Analysis of the concentrations of volatile organic compounds (VOCs) in breath with an acceptable accuracy are assessed by means of using analytical techniques with high sensitivity, accuracy, precision, low response time, and low detection limit, which are desirable characteristics for the detection of VOCs in human breath. “Breath fingerprinting”, indicative of a specific clinical status, relies… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
183
2
8

Year Published

2016
2016
2021
2021

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 258 publications
(195 citation statements)
references
References 169 publications
(275 reference statements)
2
183
2
8
Order By: Relevance
“…Several reviews covering laser spectroscopic techniques for breath gas analysis are available in the literature [22][23][24][25][26]. Together, these reviews provide a comprehensive overview of near-infrared (near-IR) and mid-IR laser-based breath analyzers using various spectroscopic methods, their challenges, and perspectives.…”
Section: Introductionmentioning
confidence: 99%
“…Several reviews covering laser spectroscopic techniques for breath gas analysis are available in the literature [22][23][24][25][26]. Together, these reviews provide a comprehensive overview of near-infrared (near-IR) and mid-IR laser-based breath analyzers using various spectroscopic methods, their challenges, and perspectives.…”
Section: Introductionmentioning
confidence: 99%
“…Both methane and methanol detection is of considerable interest since it is considered as a potential biomarker for different gut and stomach inflammatory diseases and colorectal and lung cancer. 3 Figure 3a) shows the measured spectrum of methane (CH 4 ) with a 100 ppm concentration in synthectic air. We clearly see the R-, Q-and P-branch of methane.…”
Section: Methodsmentioning
confidence: 99%
“…Recent research demonstrated such an approach can help differentiate between clinical patients and controls with various stages of cancer. [1][2][3] Unfortuntely cost and speed has limited its use mainly to research. The developement of a cost effective and portable platform opens the possibility of promoting breath gas analysis as a very promissing in-situ screening method.…”
Section: Introductionmentioning
confidence: 99%
“…These small alterations are on the same order as expected relative to the changes of 13 CO2 exhalation after 13 C-methacetin administration in the LiMAx test. It has been long known that alveolar gas exchange is dependent on ventilation, pulmonary perfusion, and the blood:air partition coefficient, and that breath samples are not well reproducible [12]. Thus, the 12 CO2 and 13 CO2 concentrations have to be measured at the same or on a time scale much faster than the breath cycle.…”
Section: Handling Of Breath Gasmentioning
confidence: 99%